Honey Moon - Phillips, Susan Elizabeth (New York : Pocket Books, 1993)
Challenged to retain her child star glory into adulthood, passionate Honey Jane Moon changes the destinies of Dash Coogan, who has outgrown his career ambitions, and Eric Dillon, a seductive Hollywood bad boy with a painful secret.
81233
Keywords: Actresses -- Fiction; Hollywood (Calif.) -- Fiction; Love stories